Success Of Small-Medıum Mıcro Industrıal Busıness Management Based On Busıness Envıronment, Busıness Management, Creatıvıty And Innovatıon In West Java Provınce Indonesıa - Dwi Gemina; Sri Harini; Endang Silaningsih (APMBA (Asia Pacific Management and Business Application), 2021)
The Micro, Small, and Medium industries (MSMI) have an essential role as a driver of the economy in Indonesia. The sector MSMI opportunities can provide employment that can reduce unemployment and contribute to Gross Domestic Product (GDP). In addition, several types of products from this sector through exports contribute to generating foreign exchange. The objectives of this study: 1) analyze the direct and indirect effects of the business environment and business management on creativity and innovation and business success; 2) analyze the factors driving and inhibiting creativity and innovation; 3) analyze the factors driving and inhibiting business success: survey research methods and forms of descriptive and verification research. The research object of MSMI snack food in West Java Province was 150 respondents. Sampling using technique random sampling is based on areas that have the potential for industrial development (industrial centers) consisting of three areas, namely Bogor, Sukabumi, and Cianjur, which have a large number of  MSMI  with superior products that have potential and become priorities for development. This research used the analysis technique SEM or Structural Equation Modeling. The results show that there are direct and indirect effects of the business environment, business management on creativity and innovation as well as business success; the driving factors for creativity and innovation as well as business success are the business environment and business management.